How Positively Valenced Health Messages can Foster Information Selection: Evidence from Two Experiments - Ort, Alexander; Siegenthaler, Perina; Fahr, Andreas (Frontiers in Communication, 2021)
Objective: Positively valenced appeals have received comparably less attention than negative appeals. However, messages utilizing negative emotions have been repeatedly criticized, and research has demonstrated the beneficial effects of applying positive emotionally-charged messages. Therefore, this study investigates the impact and effectiveness of positive to negative messages. Design: In two studies (N1 = 108, N2 = 355), participants were exposed to one video about healthy eating and exercising, which was manipulated concerning valence (positive vs. negative). Main Outcome Measures: We assessed efficacy perceptions and attitudes towards healthy eating and exercising as well as participants’ selection of topic-related information on a mock-up website immediately after message exposure. Results: A positive emotional experience led to stronger efficacy perceptions, which promoted attitudes towards the displayed behavior but not information selection (Study 1). A more diverse sample in a follow-up replication (Study 2) substantiated these findings. Additionally, it demonstrated that being affected by a health issue has a decisive influence on the selection of information. In particular, a higher BMI negatively influenced information selection when efficacy perceptions were high. Conclusion: The study demonstrates the double-edged nature of strengthening efficacy expectations, as they can promote healthy attitudes and provide affected individuals with a false sense of security.